2000
DOI: 10.1111/j.1475-2743.2000.tb00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the 1995–1997 drought on nitrate leaching in lowland England

Abstract: The effect of drought between summer 1995 and 1997 on stream and river nitrate concentrations was investigated using sites close to the long-running meteorological station in Oxford, UK. Nitrate concentrations in the River Windrush were relatively low during the drought, but after it had ended reached the highest level since records began in 1973. The low concentrations during the drought probably reflect a reduced contribution from agricultural runoff. High nitrate concentrations were found in a field drain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 17 publications
4
30
0
Order By: Relevance
“…Because point sources were absent, these results suggested reduced input from non‐point sources during low‐flow periods. Evidence for reduced loads during low‐flow due to changed water origin compared to normal conditions was also found elsewhere (Baures et al, ; Burt & Worrall, ; Burt, Worrall, Howden, & Anderson, ; Foster & Walling, ; Morecroft, Burt, Taylor, & Rowland, ; Zielinski, Gorniak, & Piekarski, ).…”
Section: Introductionsupporting
confidence: 67%
“…Because point sources were absent, these results suggested reduced input from non‐point sources during low‐flow periods. Evidence for reduced loads during low‐flow due to changed water origin compared to normal conditions was also found elsewhere (Baures et al, ; Burt & Worrall, ; Burt, Worrall, Howden, & Anderson, ; Foster & Walling, ; Morecroft, Burt, Taylor, & Rowland, ; Zielinski, Gorniak, & Piekarski, ).…”
Section: Introductionsupporting
confidence: 67%
“…Although the annual memory effect does not appear to be statistically significant at the 0.2 level (Figure 1a), many previous observational studies demonstrated that just one year or even shorter dry periods followed by high rainfalls can lead to high DN-load anomalies and eutrophication, such as marked rises of river nitrate-N concentrations or loads [e.g., Foster and Walling, 1978;Morecroft et al, 2000;Kaushal et al, 2008] and phytoplankton production [e.g., Acker et al, 2005]. Furthermore, the statistical significance may be low due to the short-term ) N data availability, which excludes historically the most dry (1960s) and wet (1970s) periods.…”
Section: The Influence Of Climate Variability On River Dn-load Anomaliesmentioning
confidence: 87%
“…The effects of drought can be different if drought increases in a currently dry area or in an area that is not currently water limited and if drought does not cause drastic changes in these situations. Drought tends to increase mineralization and nitrification in the UK, probably because of an increase of oxygen in soils and because of increases in nitrate loads in runoff (Morecroft et al, 2000). The most frequent effect observed after droughts in temperate forests is an increase of nitrate concentrations in runoff after the first rain following a drought, with the nitrates coming mainly from superficial runoff, but from subsurface runoff after subsequent rainfall (Lange and Haensler, 2012).…”
Section: Climate Changementioning
confidence: 99%